Finanční gramotnost žáků víceletého gymnázia - Nováková, Kateřina (2015)
The diploma thesis "Financial literacy of pupils at grammar school" deals with the attitudes of students to the issue of financial literacy and the level of their knowledge. It focuses on individual components of financial literacy and key factors which influence and shape the students' knowledge and attitudes. Comparing available literature sources the definition of financial literacy is discussed in the theoretical part. The theoretical part also includes the way financial education is regulated in the Czech Republic. The practical part using a descriptive statistical analysis presents results received from the questionnaire distributed among pupils of the grammar school. Based on the results four hypotheses were set and their validity is tested. The evaluation and discussion parts are incorporated in the work.